2003
DOI: 10.1071/ea01130
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ploidy and seed mass on the emergence and early vigour of perennial ryegrass (Lolium perenne L.) cultivars

Abstract: Abstract. Genetic variation for seed mass and components of early vigour were measured on 120 seedlings of each of 18 diploid and 27 tetraploid perennial ryegrass (Lolium perenne L.) cultivars. Seeds of tetraploid cultivars were on average heavier (3.8 mg) than seed of diploid cultivars (2.4 mg). However, there was variation for mean seed mass both within and between ploidy classes and within cultivars. The components of early vigour measured on each of the seedlings were: date of emergence, leaf appearance ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
6
20
0
3
Order By: Relevance
“…Hexaploid plants had higher fresh weights and were on average 44.35% larger than triploid plants. This finding is consistent with the reports that polyploids are often associated with superior agronomic traits such as an increase in leaf thickness (Sugiyama, 1998;Kermani et al, 2003;Shao et al, 2003;Vyas et al, 2007), larger and fewer leaves and tillers than the parental lines (Smith et al, 2000;Sugiyama, 2005), higher width/length ratios, a more compact growth habit (Kermani et al, 2003;Allum et al, 2007), and increased biomass, yield, and disease resistance (Osborn et al, 2003;Comai, 2005;Zhang et al, 2010a). It has been suggested that stronger stems, thicker leaves, and changes to the density and sizes of stomata in polyploid plants are associated with improved abiotic tolerance (Huang et al, 2001;Saleh et al, 2008) and with higher genetic adaptability and tolerance to environmental stresses (Xiong et al, 2006).…”
Section: Impact Of Chromosomal Doubling On Morphological Characteristicssupporting
confidence: 92%
“…Hexaploid plants had higher fresh weights and were on average 44.35% larger than triploid plants. This finding is consistent with the reports that polyploids are often associated with superior agronomic traits such as an increase in leaf thickness (Sugiyama, 1998;Kermani et al, 2003;Shao et al, 2003;Vyas et al, 2007), larger and fewer leaves and tillers than the parental lines (Smith et al, 2000;Sugiyama, 2005), higher width/length ratios, a more compact growth habit (Kermani et al, 2003;Allum et al, 2007), and increased biomass, yield, and disease resistance (Osborn et al, 2003;Comai, 2005;Zhang et al, 2010a). It has been suggested that stronger stems, thicker leaves, and changes to the density and sizes of stomata in polyploid plants are associated with improved abiotic tolerance (Huang et al, 2001;Saleh et al, 2008) and with higher genetic adaptability and tolerance to environmental stresses (Xiong et al, 2006).…”
Section: Impact Of Chromosomal Doubling On Morphological Characteristicssupporting
confidence: 92%
“…The highest values of cell size were recorded in tetraploid genotypes, as reported by Smith et al (2003) who noted that polyploidy increased the cell size and volume. Decreased cell number in polyploid genotypes was compensated by increased cell size as reported by Doonan (2000) and Inze and De Veylder (2006).…”
Section: Discussionsupporting
confidence: 58%
“…Tetraploidization of Chaenomeles japonica reduced seed set but increased the proportion of fruit flesh (Stanys et al 2006), while seed weight of ryegrass tetraploids was adequately higher (Dewey 1980). Also, tetraploid Lolium perenne and Lolium multiflorum were noted to have larger but fewer leaves and tillers than its diploid relatives (Smith et al 2003;Sugiyana 2005). Tetraploidization of Zizyphus jujube, an economically important fruit tree in Asia, resulted in thicker stems, rounder and succulent leaves, larger flowers and a delay in flowering time of 3-4 days (Gu et al 2005).…”
Section: Applications Of In Vitro Chromosome Doubling In Plant Breedingmentioning
confidence: 99%